Problems Posed by Prospective Elementary Mathematics Teachers in the Concept of Functions: An Analysis Based on SOLO Taxonomy - İnci̇kabi, Lutfi; Bi̇ber, Abdullah Çağrı (Mersin University Journal of the Faculty of Education, 2016)
Abstract: The aim of this study is to carry out an analysis according to SOLO-taxonomy about problem posing knowledge of prospective elementary mathematics teachers on mathematical functions. The methodology adopted in the current study was a case study. The participants of the study consisted of 67 prospective elementary mathematics teachers. According to the findings of the study, the knowledge of the prospective elementary mathematics teachers on functions in mathematics is open to development through proper teaching methods. Moreover, the majority of their knowledge levels have been grouped as pre-structural level, multi-structural level and relational level while only a few of their knowledge levels were at extended abstract level. Based on the results, it might be beneficiary to train prospective mathematics teachers who can creatively use problem posing activities in their classrooms and who will become a model for their students with their problem-posing performances to overcome their conceptual deficiencies concerned with functions. Keywords: Mathematical knowledge, problem posing, prospective mathematics teachers, SOLO taxonomy
Keywords: 4. Education